Comparative Clinical Outcomes With Scale-up of Dolutegravir as First-Line Antiretroviral Therapy in Ukraine. (1st October 2022) - Dumchev, Kostyantyn; Kiriazova, Tetiana; Riabokon, Serhiy; Shost, Alyona; Parrish, Canada; Shapoval, Anna; Germanovych, Myroslava; Penner, Jeremy; Beste, Jason; Puttkammer, Nancy
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Achievement of the UNAIDS 95-95-95 targets requires ARV regimens that are easy to use, well-tolerated, and cost-effective. Dolutegravir (DTG)-based regimens are efficacious and less costly than other common first-line regimens. This study assessed real-world effectiveness of DTG regimens in treatment-naive people living with HIV in Ukraine. Methods: We extracted data from the national Medical Information System on all adult patients who initiated antiretroviral therapy (ART) with DTG, lopinavir/ritonavir, or efavirenz (EFV) between October 2017 and June 2018, at 23 large clinics in 12 regions of Ukraine. Viral suppression at 12 ± 3 months and retention at 12 months after treatment initiation were the outcomes of interest. Results: Of total 1057 patients, 721 had a viral load test within the window of interest, and 652 (90%) had viral load of ≤ 200 copies/mL. The proportion with suppression was lower in the EFV group [aOR = 0.4 (95% confidence interval: 0.2 to 0.8)] and not different in the LPV group [aOR = 1.6 (0.5 to 4.9)] compared with the DTG group. A 24-month or longer gap between diagnosis and treatment was associated with lower odds of suppression [aOR = 0.4 (0.2 to 0.8)]. Treatment retention was 90% (957/1057), with no significant difference by regimen group. History of injecting drug use was associated with decreased retention [aOR = 0.5 (0.3 to 0.8)]. Conclusions: DTG-based regimens were comparable with LPV and more effective than EFV in achieving viral suppression among ART-naive patients in a multisite cohort in Ukraine. Treatment retention was equally high in all 3 groups. This evidence from Ukraine supports the ART Optimization Initiative as a strategy to improve efficiency of the ART program without negatively affecting patient clinical outcomes.